Organizational structure changes within the banks - Valentina Angelkoska (UTMS Journal of Economics, 2021)
For successful operation, banks are constantly implementing changes in their organizational structure. These changes are due to various internal and external factors. Organizational structures within the banks are complex and specific for the banking sector, as well as for each bank. In this paper, organizational structures of several banks will be analyzed. Contemporary trends will be illustrated with the organizational structures of few international banks. As a case study, the changes in the organizational structure of one the biggest banks in the Republic of North Macedonia will be analyzed.
Keywords: G21; L22; 330; banks; organizational structures; change management